The correct answer is B)x =
.
In order to find this, we need for follow the order of operations.
y - p = m(x - q) ----> Divide both sides by m
= x - q ----> add q to both sides
= x ---> now we need to give it a common denominator. Multiply the q term by m/m
= x
This is our final answer.
Answer:
2x² + 8x - 35
Step-by-step explanation:
x(2x + 3) + 5(x - 7) ← distribute both parenthesis
= 2x² + 3x + 5x - 35 ← collect like terms
= 2x² + 8x - 35
22382. You just multiply 1178 and 19 :-)
Answer:
I cant see the photo
Step-by-step explanation:
sorry
Answer:
f^-1(x)= -x/5 - 4/5
Step-by-step explanation: